A PRODUÇÃO DE SENTIDOS SOBRE A CULTURA INFANTIL E A REPRESENTAÇÃO PROFESSOR/ALUNO NO LIVRO „CAZUZA‟ NO INÍCIO DO SÉCULO XX - ARGEL, Aurineide de Aguiar Silva (2023)
The book 'Cazuza', written by Viriato Corrêa, from the state of Maranhão, at the beginning of the 20th century, brings in its structure a children's narrative about the educational field. In it, it is possible to follow the trajectory of the boy Cazuza, the protagonist of the book, which is autobiographical and fictionalized, through his first years of schooling. He starts his student life attending the village school, with an authoritarian education that had the palmer as a "motivational tool"; then, when his parents move, he goes to the Village school, which has a teacher trained in the state capital and presents a more affective and humanistic education; and, finally, he arrives at the Capital's school, São Luís, with a more diverse education, where social aspects were more highlighted, such as social, economic, and racial discrimination. The research we undertake involves the universe of children's culture in which the narrative takes place, as well as the teachers' knowledge and the production of meaning that the book effects in relation to children's education in Maranhão at the beginning of the 20th century. The primary purpose of the research is to scrutinize the discourse formation of children's culture in the academic milieu, within the context of pedagogical practices. The objectives of this study are as follows: a) to exhibit the impact of teachers' social representations of childhood culture on children's development; b) to determine how the production of meanings by participants in the educational system shapes the pedagogical practices; c) to provide a comparative analysis of pedagogical practices across different contexts at the start of the century. This study explores concepts in Education, Childhood Sociology, Education History, and Discourse Analysis by authors including Almada (2018), Corsaro (2011), Quinteiro (2009), Pimenta (2012), Andrade (1984) Silva (2015), Mussalim (2012); Foucault (1970), Aroche, Pêcheux, Henri (2020). And, among the concepts ploughed from the field of French Line Discourse Analysis and that help to understand the discursive production of the book, are those of Ideological Formation (IF) and Discursive Formation (FD). The work focuses on the discursive materiality, formed by the excerpts chosen from the original work (the book 'Cazuza', by Viriato Corrêa) to, from there, evaluate the threads of discourse that the narrative of the book Cazuza presents, and how this discourse is determined by the ideological formation of positivism, in education, of progress, in society, and of meritocracy, in personal relationships. And also how it is inserted in the field of discursive formations of the beginning of the century, which value discipline, encyclopedism, order to achieve a desired end, in a directly intrinsic relationship with the FI's. Finally, it appears that the educational environment in Maranhão, as seen in the narrative of the character Cazuza, as well as in other states, mirrored the difficulties inherent in the social context, making it possible to perceive, in the discursive formations, the ideological aspects that involved the relationships socio- educational at the beginning of the century.